Turbulent structure of the impact of a ground vortex flow - Vieira, Diana Filipa da Conceição (2015)
Turbulent jets impinging on flat surfaces through a low-velocity crossflow are typical of the flow beneath a short/vertical take-off aircraft which is lifting off or landing with zero or small forward momentum1. Ground effect may occur and change the lift forces on the aircraft, cause reingestion of exhaust gases into the engine intake and raise fuselage skin temperatures. In this latter application the impingement of each downward-directed jet on the ground results in the formation of a wall jet which flows radially from the impinging point along the ground surface. The interaction of this wall jet with the free stream results in the formation of a “ground vortex” far upstream of the impinging jet, which has profound implications on the aircraft design. In addition the collision of the wall jets originates a fountain upwash flow, affecting the forces and moments induced in the aircraft when operating in ground effect. Improved knowledge of impinging flows is therefore necessary to avoid these effects and to be able to model a range of jet-impingement type of applications with practical interest. Recently there have been some reports of studies focused on one or multiple jets configurations to understand the phenomena associated with this type of complex flows, revealing this studies great importance to the Harrier/ AV-8B aircraft. This work is dedicated to a detailed analysis of the complex flow field beneath 2 impinging jets aligned with a low-velocity crossflow relevant for the future F-35 VSTOL configuration, and provides a quantitative picture of the main features of interest for impingement type of flows.